Phytochemical Studies On Polygonum Glabrum (Willd.) - P. SIVAKUMAR; K.L.SENTHILKUMAR; J. PRAVEEN VARMA; J. PRAVEEN VARMA (International Journal of Pharma and Bio Sciences, 2011)
The plant Polygonum glabrum (willd.) belonging to the family Polygonaceae. The plant mostly found in river banks, stream sides and marshy areas. It is found as dense clumps and the plants are sub shrubs and growing up to 2.5 cm. The root stocks are reported to be used in piles, jaundice, debility and consumption. The herb possess anti bacterial activity against micrococcus pyrogens and diplococcus pyrogens. Some naturally occurring flavonoids like kaemphferol-3-methyl ester, quercetrin, quercetin shows anti fungal activity. Four new diesters isolated from 2, 3 dihydroxy hydramine were isolated from the herb having anthelmentic activity in traditional medicine. The anatomical and macroscopical work was done and used for the identification of the plant. The phytochemical screenings of chloroform extract shows the presence of chemical compounds like alkaloids, glycosides, carbohydrates and flavonoids. The spectral studies like U.V and FTIR are the preliminary work for the detection of some alkaloidal contents in the plant. The chromatographic studies shows various spots (Paper/Hptlc) with chloroform extract may confirm the presence of alkaloidal contents in the plant.